GEN-8 COMPREHENSIVE WHOLE GENOME SEQUENCING ANALYSIS ELUCIDATES STRUCTURAL VARIANTS IN MEDULLOBLASTOMA. (3rd December 2022) - Funakoshi, Yusuke; Nakashima, Takuma; Uneda, Atsuhito; Yoshimoto, Koji; Narita, Yoshitaka; Suzuki, Hiromichi
Abstract: Introduction: Medulloblastoma is the most common malignant pediatric brain tumor with a poor prognosis. International collaborative efforts for sequencing the genomes of medulloblastomas have delineated the landscape of coding mutations. However, little is yet known about structural variants (SVs). Here, we analyzed whole-genome sequencing (WGS) data of medulloblastoma to reveal the comprehensive genetic aberrations, including SVs. Methods: We collected and analyzed publically available WGS data of 432 cases with medulloblastoma from MAGIC consortium, ICGC, and St Jude cloud. Results: The median coverage is 36.4x with no difference among cohorts. The median number of SV per case is 1.0 (WNT), 5.0 (SHH), 6.0 (Group 3), and 5.0 (Group 4), respectively. SHH medulloblastoma with TP53 mutation has significantly a greater number of SVs (77.0/sample), suggesting that genome instability by TP53 mutations gives rise to SVs. At least one SV involved in already known driver genes in 10.9% of the SHH cases, supporting a model where SV could lead to tumor initiation. Since some of those SVs are caused by copy-neutral translocation, detecting those alterations is challenging by other than WGS. Complex SVs involving TERT focal amplification are identified in 11.5% of the SHHα subtype which usually does not have TERT promoter mutation. Although TERT promoter mutation is enriched predominantly in the SHHδ subtype, overexpression of TERT may be necessary for tumor maintenance in some of the SHHα cases. Unbalanced amplifications are commonly observed in known drive genes such as PPM1D, CCND2, and PVT1 where a part of exons are exclusively amplified, implying that functionally important regions are selectively altered by SVs which could promote tumor development. Conclusions: SV affects not just copy number changes but also the structure of the genome, where breakpoints exist based on gene function and regulations. SVs along with genetic mutations contribute to medulloblastoma pathogenesis.